COVID-19: Anthropocene and Capitalocene Caused Pandemics - Subedi, Madhusudan (Dhaulagiri Journal of Sociology and Anthropology, 2020)
Most epidemiological studies focus on the direct causes of diseases while wider, social causal factors are ignored. This paper briefly highlights the history of major epidemics and the role of Anthropocene and Capitalocene for the emergence and reemergence of pandemics like COVID-19. Books, journal articles, and statistics offer information that can explain the phenomena. A historical inquiry can inform us about the fundamental causes of pandemics. Human security and ecology are intertwined, and the global effect of pandemics responded to at the national level is inadequate. The lessons from the past and present help us devise effective ethically and socially appropriate strategies to mitigate the threats. If the present crisis is not taken seriously at the global level, the world has to face more difficult challenges in years to come.